2020
DOI: 10.1002/itl2.194
|View full text |Cite
|
Sign up to set email alerts
|

An efficient path planning GLOSA‐based approach over large scale and realistic traffic scenario

Abstract: Vehicle speed and trajectories play an important role in influencing fuel consumption, gas emissions and travel time. ITS services are often proposed in order to reduce the impact of these issues on the environment and the comfort of drivers. Cooperative Intelligent Transport Systems (C‐ITS) introduced many services that target traffic efficiency management and road safety. Green Light Optimal Speed Advisory (GLOSA) is one of the traffic efficiency services that can significantly cut fuel consumption and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…According to Sharara [9], this method attempts to improve overall traffic safety, reduce congestion, and improve driving comfort. The use of GLOSA-based route planning algorithms inside C-ITS, as evidenced by studies such as those done by Karoui et al [10], demonstrates a balanced strategy that results in reduced travel time and fuel savings for drivers.…”
Section: Introductionmentioning
confidence: 94%
“…According to Sharara [9], this method attempts to improve overall traffic safety, reduce congestion, and improve driving comfort. The use of GLOSA-based route planning algorithms inside C-ITS, as evidenced by studies such as those done by Karoui et al [10], demonstrates a balanced strategy that results in reduced travel time and fuel savings for drivers.…”
Section: Introductionmentioning
confidence: 94%
“…A noteworthy example is algorithms aimed at route traffic or at finding network topologies which balance the energy consumption of nodes with the target to increase the network lifetime 3 . Research about path planning is aimed at obtaining a better routing, which usually has a relevant and positive impact on power consumption 4‐6 . All these aspects are more complex if mobility of nodes is considered.…”
Section: Current and Future Trendsmentioning
confidence: 99%
“…The fourth paper “An efficient path planning GLOSA‐based approach over large scale and realistic traffic scenario” 6 analyzes path planning of moving vehicles, with the main target to decrease waiting and travel times, but without significantly impacting fuel consumption. One of the main innovations of this work consists in including the impact of traffic lights in the selection process of the fastest route (performed through the Dijkstra algorithm).…”
Section: In This Special Issuementioning
confidence: 99%
“…For example, see the studies by Xia et al ( 12 ) and Chen et al ( 13 ). Karoui et al ( 14 ) investigated a path planning GLOSA-based simulation approach in a large-scale and realistic scenario. Their simulation study carried out under free-flow and peak-hour conditions showed that GLOSA offers a balanced scale between travel time reduction and fuel savings.…”
Section: State Of Knowledgementioning
confidence: 99%